MACULOPATHY AFTER TRANSPUPILLARY THERMOTHERAPY FOR CHOROIDAL MELANOMAS - A. F. Brovkina; A. E. Zargaryan (Опухоли головы и шеи)
Macular area changes arising after transpupillary thermotherapy for extrafoveal choroidal melanomas were studied in 23 patients. Risk factors for this complication were identified; these were the tumor margin being close (1−4.5 mm) to the foveola; temporal localization of melanoma; eyeground comorbidity (age-related macular degeneration, high-grade myopathy).